Chse Based Information Technology Implementation Through We Love Bali Application - P, Kadek Wulandari Laksmi; Permana, Putu Indra; Ariwangsa, I G. N. Oka; Lasmi, Ni Wayan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The We Love Bali program is a program created by the Ministry of Tourism and Creative Economy with the aim of inviting travel business actors in the Province of Bali to grow and develop in the midst of adapting to new habits while still paying attention to health protocols. This activity is supported by programs that can make tourists interested in the state of tourist destinations in Bali. It is hoped that this program will be something that can make tourism and the Bali economy recover which in the future can make people return to normal activities in the midst of the Covid 19 pandemic. What we use to measure the level of implementation of this program is by means of literature studies which we strengthen with qualitative methods ( interview). By referring to the qualitative descriptive results which emphasize interviews with tourism actors and are supported by data from tourists visiting Bali. These results indicate that the We Love Bali program is able to restore the economic situation of the Balinese people to a better state. And also the We Love Bali program is one of the programs implemented to help tourism and creative economy businesses including hotels, travel businesses, transport businesses, tour guides, restaurants, tourist destinations, MSMEs, and others